2020
DOI: 10.3390/ijms21072517
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Identification of Genes Affecting the Pharmacokinetics of Tacrolimus Using the DMETTM Plus Platform

Abstract: Tacrolimus is an immunosuppressive drug with a narrow therapeutic index and larger interindividual variability. We identified genetic variants to predict tacrolimus exposure in healthy Korean males using machine learning algorithms such as decision tree, random forest, and least absolute shrinkage and selection operator (LASSO) regression. rs776746 (CYP3A5) and rs1137115 (CYP2A6) are single nucleotide polymorphisms (SNPs) that can affect exposure to tacrolimus. A decision tree, when coupled with random forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…89 These results are promising but research is needed before the broader utility of ML for antibiotic discovery via molecule repurposing can be considered established. 91 Their results…”
Section: Studies Of the Pk/pd And Poppk Of Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…89 These results are promising but research is needed before the broader utility of ML for antibiotic discovery via molecule repurposing can be considered established. 91 Their results…”
Section: Studies Of the Pk/pd And Poppk Of Antibioticsmentioning
confidence: 99%
“…CART outperformed all other ML methods with a mean absolute error of 0.73 (95% CI: 0.63–0.82). Gim et al compared CART, RFR, and least absolute shrinkage and selection operator for determining the influence of single nucleotide polymorphism (SNP) for predicting of tacrolimus Cmax and AUC in healthy Korean males 91 . Their results showed that all ML methods identified CYP3A5 SNP, rs 776746 as the best predictor of tacrolimus exposure.…”
Section: Applications Of ML In Pharmaceutical Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial intelligence (AI) has been used to assist the discovery of a range of different genetic factors in humans and has helped the identification of novel SNPs associated with drug response when treating cancer, psychiatric disease, and cardiovascular disease [ 25 , 26 ]. In a previous study, AI machine learning failed to predict the platelet reactivity since very complex non-linear phenomena of platelet reactivity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%